Carboxylesterase 2 Is a Fatty Acid Ethyl Ester Synthase. Issue 4 (8th February 2017) - Tseng, Yu‐Wei; Lin, Chueh‐Yu; Tsai, Chung‐Lin; Chou, Tsong‐Yung; Hung, Chih‐Huang; Kuo, Ching‐Hua; Lai, Shang‐Chi; Tzeng, Yin‐Jeh
Abstract: Alcoholic beverages are consumed in high volumes globally, and the absorbed ethanol is metabolized by oxidative and non‐oxidative pathways. Although the latter pathways are minor, the resulting accumulation of fatty acid ethanol esters (FAEEs) has been implicated in organ damage and dysfunction, including in the liver and the pancreas. Carboxylesterase 2 (CES2) has not yet been characterized as a FAEE synthase versus several identified esterase. In this study, we aim to determine whether CES2 synthesizes FAEE from palimitic acid (PA) and ethanol. Mouse recombinant CES2 protein was mixed with PA and deuterated ethanol (EtOD) and the production of FAEE was monitored using GC/MS. The results showed that deuterated palmitic acid ethyl ester (PAEED) was produced, with EtOD concentration‐ and time‐dependent yields. At a constant palmitic acid concentration of 4 mM, the apparent Km and Vmax values for ethanol and for PAEED synthesis were 898.1 mM and 36.5 pM/min respectively. The protein structure and active site of CES2 was predicted using sequence alignments with well characterized CES1. Although the amino sequence of CES2 shares only 45 % identity with human carboxylesterase 1 (hCES1), the main domain and active site are conserved. We made a docking simulation and thus speculate that CES2 is a FAEE synthase with a similar catalytic mechanism to CES1. These data provide an important first step in vivo for pathological and therapeutic studies of FAEE‐mediated organ damages. Abstract : After alcohol consumption, a less known non‐oxidative reaction starts to metabolite the ethanol (EtOH) into fatty acid ethyl esters (FAEEs) by esterification with fatty acids. In present research, we found that mouse carboxylesterase 2 (mCES2) is able to synthesize palmitic acid ethyl ester (PAEE) from EtOH and palmitic acid (PA). CES2 is mostly studied for its hydrolyzation of 4‐methylumbelliferyl acetate, 6‐monoacetylmorphine, and irinotecan; however, the computational docking reveals that mCES2 favors the esterification of EtOH with PA rather than the reverse reaction, hydrolyzation of PAEE into PA and EtOH.